2010
DOI: 10.1029/2010tc002750
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic setting of the South China Block in the early Paleozoic: Resolving intracontinental and ocean closure models from detrital zircon U-Pb geochronology

Abstract: Zircon U‐Pb geochronological data on over 900 zircon grains for Cambrian to Silurian sandstone samples from the South China Block constrain the pre‐Devonian tectonic setting of, and the interrelationships between, the constituent Cathaysia and Yangtze blocks. Zircons range in age from 3335 to 465 Ma. Analyses from the Cathaysia sandstone samples yield major age clusters at ∼2560, ∼1850, ∼1000, and 890–760 Ma. Zircons from the eastern and central Yangtze sandstone samples show a similar age distribution with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
282
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 366 publications
(315 citation statements)
references
References 67 publications
13
282
1
Order By: Relevance
“…The final amalgamation along the Wuyi-Yunkai domain is roughly synchronous with the deformation of the East Ghats of India (∼960 Ma) and the northern Prince Charles Mountains of East Antarctica (∼990-960 Ma; e.g., Boger et al, 2000;Jayananda et al, 2000). These relationships, combined with the biogeographic consistency of the eastern SCB with Australia and the late Neoproterozoic tectonic relationship with India (e.g., Wang and Li, 2003;Yang et al, 2004;Myrow et al, 2006Myrow et al, , 2009Wang et al, 2010b), suggest to us that the SCB was situated along the margin of Rodinia between Australia and East Antarctica (e.g., Hoffman, 1991;Yang et al, 2004), as shown in Fig. 17.…”
Section: An Exterior Accretionary Orogen For the Scb Along The Marginmentioning
confidence: 99%
See 2 more Smart Citations
“…The final amalgamation along the Wuyi-Yunkai domain is roughly synchronous with the deformation of the East Ghats of India (∼960 Ma) and the northern Prince Charles Mountains of East Antarctica (∼990-960 Ma; e.g., Boger et al, 2000;Jayananda et al, 2000). These relationships, combined with the biogeographic consistency of the eastern SCB with Australia and the late Neoproterozoic tectonic relationship with India (e.g., Wang and Li, 2003;Yang et al, 2004;Myrow et al, 2006Myrow et al, , 2009Wang et al, 2010b), suggest to us that the SCB was situated along the margin of Rodinia between Australia and East Antarctica (e.g., Hoffman, 1991;Yang et al, 2004), as shown in Fig. 17.…”
Section: An Exterior Accretionary Orogen For the Scb Along The Marginmentioning
confidence: 99%
“…Li et al, 2010c;Wang et al, 2012b,c). Recent geochronological data have shown that the Neoproterozoic and even Paleozoic units are additionally presented within the previously mapped basement succession (e.g., Li et al, 1998;Wang et al, 2007cWang et al, , 2010bWang et al, , 2011bWang et al, , 2012cWan et al, 2007Wan et al, , 2010Yu et al, 2009Yu et al, , 2010Li et al, 2010aLi et al, ,c, 2011. Within the Cathaysia basement, there are small amounts of mafic and ultramafic rocks (e.g., amphibolite, metagabbro, metadiabase, metabasite, peridotite and pyroxenite), which occur mainly as lens, pods and fragments (e.g., Fujian BGMR, 1985;Guangxi BGMR, 1985;Guangdong BGMR, 1988;Zhejiang BGMR, 1989;Zhang et al, 2012a).…”
Section: Geological Background and Petrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread, intense Yanshanian granitic magmatism and mineralization in South China have attracted attention of geologists (Jahn et al, 1976;Charvet et al, 1994;Lan et al, 1996;Sewell and Campbell, 1997;Wang et al, 2010bWang et al, , 2011aWang et al, , 2011b. However, the tectonic regime responsible for the Yanshanian magmatism and related W-Sn mineralization is still debated.…”
Section: Geodynamics For W-sn Metallogenymentioning
confidence: 99%
“…Detrital zircons with the age cluster of 1700-1200 Ma are widely reported for (meta)sedimentary rocks in both the Yangtze and the Cathaysia Blocks of South China ( Fig. 9b and c; Li et al, 2007;Greentree et al, 2006;Wang et al, 2007aWang et al, , 2010bWang et al, , 2012aWang et al, , 2013bWang et al, , 2014aYu et al, 2008Yu et al, , 2010Sun et al, 2009;Zhou et al, 2009;Wan et al, 2010;Wu et al, 2010;Duan et al, 2011;Yao et al, 2011Yao et al, , 2012Xu et al, 2012;Cawood et al, 2013b). However, rocks with this age range rarely occurred in the South China, except for the metamorphosed volcanic rocks with ages of ca.…”
Section: Provenancementioning
confidence: 99%